Novel Spin–Orbit Torque Generation at Room Temperature in an All‐Oxide Epitaxial La0.7Sr0.3MnO3/SrIrO3 System. Issue 24 (7th May 2021) - Huang, Xiaoxi; Sayed, Shehrin; Mittelstaedt, Joseph; Susarla, Sandhya; Karimeddiny, Saba; Caretta, Lucas; Zhang, Hongrui; Stoica, Vladimir A.; Gosavi, Tanay; Mahfouzi, Farzad; Sun, Qilong; Ercius, Peter; et al.
Abstract: Spin–orbit torques (SOTs) that arise from materials with large spin–orbit coupling offer a new pathway for energy‐efficient and fast magnetic information storage. SOTs in conventional heavy metals and topological insulators are explored extensively, while 5d transition metal oxides, which also host ions with strong spin–orbit coupling, are a relatively new territory in the field of spintronics. An all‐oxide, SrTiO3 (STO)//La0.7 Sr0.3 MnO3 (LSMO)/SrIrO3 (SIO) heterostructure with lattice‐matched crystal structure is synthesized, exhibiting an epitaxial and atomically sharp interface between the ferromagnetic LSMO and the high spin–orbit‐coupled metal SIO. Spin‐torque ferromagnetic resonance (ST‐FMR) is used to probe the effective magnetization and the SOT efficiency in LSMO/SIO heterostructures grown on STO substrates. Remarkably, epitaxial LSMO/SIO exhibits a large SOT efficiency, ξ|| = 1, while retaining a reasonably low shunting factor and increasing the effective magnetization of LSMO by ≈50%. The findings highlight the significance of epitaxy as a powerful tool to achieve a high SOT efficiency, explore the rich physics at the epitaxial interface, and open up a new pathway for designing next‐generation energy‐efficient spintronic devices. Abstract : An all‐oxide, SrTiO3 //La0.7 Sr0.3 MnO3 (LSMO)/SrIrO3 (SIO) heterostructure with lattice‐matched crystal structure is synthesized, exhibiting an epitaxial and atomically sharp interface between the ferromagnetic LSMO and the high spin–orbit‐coupled metal SIO. Remarkably, epitaxial LSMO/SIO exhibits a large spin–orbit torque efficiency, ξ|| = 1, while retaining a reasonably low shunting factor and increasing the effective magnetization of LSMO by ≈50%.